Zigzag Pattern Metamaterial Structure With Rectangular Patch Antenna “This paper has been withdrawn” - Bhartiya, Vishav Gaurav; Shrivastava, Laxmi (International Journal of Engineering and Technology, 2012)
“This paper has been withdrawn”